Un encuentro con el modelo de Milán y su evolución - Venus María Piedad Bonilla Rocha (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2013)
This paper describes the evolution that has taken the Milan model in the context of the various schools or theoretical-methodological approaches that have emerged in the study and treatment of families in the late sixties and early seventies, approaches that share the foundation of systems theory and cybernetics of Bateson. To understand the features and changes that have been the model should review their estate at the Mental Research Institute (MRI) in Palo Alto, California, where psychoanalytic heritage in the treatment of mental illness was gradually enriched with systemic constructs, changing the way of addressing the patient and the concepts of health and disease during treatment, resulting, over time, the consolidation model as a viable therapeutic alternative.